Overexpression of the Soybean NAC Gene GmNAC109 Increases Lateral Root Formation and Abiotic Stress Tolerance in Transgenic Arabidopsis Plants - Yang, Xuefei; Kim, Moon Young; Ha, Jungmin; Lee, Suk-Ha (Frontiers in Plant Science, 2019)
NACs are plant-specific transcription factors that have crucial roles in plant development and biotic and/or abiotic stress responses. This study characterized the functions of the soybean NAC gene GmNAC109 using an overexpression construct in Arabidopsis lines. Sequence analysis revealed that GmNAC109 is highly homologous to ATAF1 (ARABIDOPSIS TRANSCRIPTION ACTIVATION FACTOR 1), which regulates biotic and abiotic stress responses. GmNAC109 protein localized to the nucleus and its C-terminal domain exhibited transcriptional activation activity. Salt, drought, and cold stresses significantly increased expression of GmNAC109 in soybean, especially in root tissues. Similarly, Arabidopsis plants overexpressing GmNAC109 were more tolerant to drought stress than wild-type Col-0 plants. Stress response-related genes, such as DREB1A (DROUGHT-RESPONSIVE ELEMENT-BINDING 1A), DREB2A, AREB1 (ABSCISIC ACID-RESPONSIVE ELEMENT BINDING PROTEIN 1), AREB2, RD29A (RESPONSIVE TO DESICCATION 29A), COR15A (COLD REGULATED 15A), ABA1 (ABSCISIC-ACID 1), ABI1 (ABA INSENSITIVE 1), and ABI5, were upregulated in GmNAC109-overexpressing transgenic Arabidopsis lines. Overexpression of GmNAC109 significantly increased lateral root formation in transgenic Arabidopsis lines. Expression of AIR3 (AUXIN-INDUCED IN ROOT CULTURES 3) and ARF2 (AUXIN RESPONSE FACTOR 2) was increased and decreased in these transgenic lines, respectively, indicating that GmNAC109 is involved in the auxin signaling pathway and thereby helps to regulate hairy root formation. Our results provide a basis for development of soybean lines with improved tolerance to abiotic stresses via genetic manipulation.